2013
DOI: 10.7322/jhgd.61234
|View full text |Cite
|
Sign up to set email alerts
|

Back Pain and the Postural and Behavioral Habits of Students in the Municipal School Network of Teotônia, Rio Grande do Sul

Abstract: Objetivos: verificar a prevalência de dor nas costas nos últimos três meses; identificar os hábitos posturais e comportamentais; e verificar se existe relação entre a dor nas costas e os hábitos de escolares do Ensino Fundamental da Rede Municipal de Ensino da cidade de Teutônia/RS. Método: trata-se de um estudo epidemiológico populacional, em que participaram 833 escolares de 5ª a 8ª séries de todas as Escolas da Rede Municipal de Ensino da cidade de Teutônia. Os escolares responderam o questionário BackPEI q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 35 publications
2
20
0
9
Order By: Relevance
“…26 In this context, it is important to note that this study included students up to 18 years old, while in the study were in Bauru only schoolchildren aged 11-14 years were evaluated, 8 similar to the age expected for scholarsenrolled in the study conducted in Teutônia, Rio Grande do Sul, with students from 5th to 8th grade. 25 Although no association was found between the variables analysed when analysing the relationship between back pain and gender among adolescents in Teresina, the ratio of prevalence of pain among boys and girls was equal to 1.12 (82% femaleversus73% in males).And, similar to what was demonstrated in this study, there was also no association between gender and back pain. 24,27 However, other studies have shown that males are less prone to experiencing back pain.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…26 In this context, it is important to note that this study included students up to 18 years old, while in the study were in Bauru only schoolchildren aged 11-14 years were evaluated, 8 similar to the age expected for scholarsenrolled in the study conducted in Teutônia, Rio Grande do Sul, with students from 5th to 8th grade. 25 Although no association was found between the variables analysed when analysing the relationship between back pain and gender among adolescents in Teresina, the ratio of prevalence of pain among boys and girls was equal to 1.12 (82% femaleversus73% in males).And, similar to what was demonstrated in this study, there was also no association between gender and back pain. 24,27 However, other studies have shown that males are less prone to experiencing back pain.…”
Section: Discussionsupporting
confidence: 73%
“…19 Regarding the prevalence of this symptom, Vitter et al 8 in a study of 1236 schoolchildren aged between 11and 14 years old in the city of Bauru, São Paulofoundthat 19.5% of respondents had low back pain.Further, in a study of 833 schoolchildren from the 5th to 8th grades in municipal schools of Rio Grande do Sul, the prevalence of back pain was found to be54.1% in the three-monthperiod before the survey. 25 The differences between the results of different studies on the prevalence of low back pain in adolescents can be partly attributed to the different methodologies used, the age of the subjects and even the geographical location of thestudies. 26 In this context, it is important to note that this study included students up to 18 years old, while in the study were in Bauru only schoolchildren aged 11-14 years were evaluated, 8 similar to the age expected for scholarsenrolled in the study conducted in Teutônia, Rio Grande do Sul, with students from 5th to 8th grade.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations